2023
DOI: 10.1007/s10668-023-03319-5
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the interplay of environmental conservation within spirituality and multicultural perspective: insights from a cross-sectional study

Koleayo Omoyajowo,
Mela Danjin,
Kolawole Omoyajowo
et al.

Abstract: The need to protect and sustain environmental resources for future generation remains sacrosanct in global sustainability agenda. This study was aimed at exploring the interplay between environmental conservation and spirituality from a multicultural perspective. While studies on “spirituality” have monumentally gained global attention, a growing number of evidence underscore the critical role of spiritual resources available for ensuring environmental stewardship. In this present study, attempt was made to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…Certainly, the implication of having the majority able to volunteer in the wide dissemination of healthy tips on possible mitigation approaches to BPA exposure would result in a massive awareness on the possible ways to reduce health risk associated with the compound. Positive attitude such as willingness to share safety information about issues of public health concern, and community participation in public health programs are widely considered as positive indicators to achieving a sustainable healthy environment (Omoyajowo et al, 2021, Omoyajowo et al, 2023. Similar study observed similar great attitude in public willingness to co-operate with the government on mitigation efforts towards reducing Microplastic pollution (Alkyildiz et al, 2015, Omoyajowo et al, 2021a.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Certainly, the implication of having the majority able to volunteer in the wide dissemination of healthy tips on possible mitigation approaches to BPA exposure would result in a massive awareness on the possible ways to reduce health risk associated with the compound. Positive attitude such as willingness to share safety information about issues of public health concern, and community participation in public health programs are widely considered as positive indicators to achieving a sustainable healthy environment (Omoyajowo et al, 2021, Omoyajowo et al, 2023. Similar study observed similar great attitude in public willingness to co-operate with the government on mitigation efforts towards reducing Microplastic pollution (Alkyildiz et al, 2015, Omoyajowo et al, 2021a.…”
Section: Discussionmentioning
confidence: 78%
“…Nigeria is Africa's most populous country (Omoyajowo et al, 2023) with a unique climate ranging from arid to humid equatorial, and with a rich deposit of valuable minerals such as crude oil, natural gas, coal, tin, columbite, and gold. This study was conducted in four metropolitan cities of Southwestern States in Nigeria.…”
Section: Materials and Methods Brief Description Of Study Locationsmentioning
confidence: 99%
See 1 more Smart Citation